Joaquim Nabuco: pan-americanismo, circulações de representações e relações de poder (1905-1910) - Fabriz, Larissa Milanezi (2014)
The following dissertation discuss the pan-Americanism representations that the brazilian Joaquim Nabuco intended to circulate by using the rhetoric as strategy while occupied the role of brazilian ambassador in Washington between the years of 1905 and 1910. It was a context in which the Foreign Relations Ministry had the purpose of orientate the diplomatic actions to the American continent and privilege the approximation with the United States of America. The text analyses how Nabuco created and took advantage of spaces of sociability such as political banquets, conferences at the north-American universities and the periodical Revista Americana to spread the image of the country Brazil as pacific, south American leader and possible ally of United States to further a Pan-American nation in the continent. The appropriations of those representations by other American intellectuals were studied to realize how they thought the continent issues to foment its modernization and balance with the purpose to guarantee the peace. The historical sources used in this research were the speeches written and spoken by Joaquim Nabuco at political banquets and conferences, news from the New York Times and The Washington Post, articles published by Joaquim Nabuco and other intellectuals at the Revista Americana, minutes of the brazilian state board and the diplomatic missives sent by the diplomat to the Foreign Relations Ministry. These sources were used to comprehend how Joaquim Nabuco formulate strategies to make possible an approach between Brazil and United States of American.